"The Actor Is Policy": Application of Elite Theory to Explore Actors' Interests and Power Underlying Maternal Health Policies in Uganda, 2000-2015 - Moses Mukuru; Suzanne N. Kiwanuka; Lucy Gilson; Maylene Shung-King; Freddie Ssengooba (Kerman University of Medical Sciences, 2021)
BackgroundThe persistence of high maternal mortality and consistent failure in low- and middle-income countries to achieve global targets such as Millennium Development Goal five (MDG 5) is usually explained from epidemiological, interventional and health systems perspectives. The role of policy elites and their interests remains inadequately explored in this debate. This study examined elites and how their interests drove maternal health policies and actions in ways that could explain policy failure for MDG 5 in Uganda. MethodsWe conducted a retrospective qualitative study of Uganda's maternal health policies from 2000 to 2015 (MDG period). Thirty key informant interviews and 2 focus group discussions (FGDs) were conducted with national policy-makers, who directly participated in the formulation of Uganda's maternal health policies during the MDG period. We reviewed 9 National Maternal Health Policy documents. Data were analysed inductively using elite theory. ResultsMaternal health policies were mainly driven by a small elite group comprised of Senior Ministry of Health (MoH) officials, some members of cabinet and health development partners (HDPs) who wielded more power than other actors. The resulting policies often appeared to be skewed towards elites' personal political and economic interests, rather than maternal mortality reduction. For a few, however, interests aligned with reducing maternal mortality. Since complying with the government policy-making processes would have exposed elites' personal interests, they mainly drafted policies as service standards and programme documents to bypass the formal policy process. ConclusionUganda's maternal health policies were mainly influenced by the elites' personal interests rather than by the goal of reducing maternal mortality. This was enabled by the formal guidance for policy-making which gives elites control over the policy process. Accelerating maternal mortality reduction will require re-engineering the policy process to prevent public officials from infusing policies with their interests, and enable percolation of ideas from the public and frontline.